Mitochondrial DMA variation in plants regenerated from embryogenic callus cultures of CMS triticale - Weigel, Ralf; Wolf, Markus; Hesemann, Claus-Ulrich (Theoretical and applied genetics, 1995)
The mitochondrial DNA (mtDNA) organization of primary hexaploid cytoplasmic male-sterile (CMS) triticale regenerants containing Triticum timopheevi cytoplasm was analysed by hybridization experiments and compared with the mitochondrial genome organization of the corresponding regenerants with maintainer cytoplasm. Callus cultures had been derived from immature embryos, and 623 triticale plants were regenerated via somatic embryogenesis after three to four subcultures. The chondriome of 159 regenerants was investigated with regard to somaclonal variation. Six different mitochondrial gene probes and four different restriction enzymes were used for Southern blot analyses by the non-radioactive digoxigenin labeling technique. Alloplasmic regenerants showed a gain or loss of hybridization signals up to a high percentage, while euplasmic ones revealed only minor variability with respect to band stoichiometries. In 24 cases rearrangements in the mtDNA were proved. We suppose that recombination processes and selective amplification events are responsible for these findings.